What works : gender equality by design - Bohnet, Iris (Cambridge, Massachusetts : The Belknap Press of Harvard University Press, 2016)
"Gender equality is a moral and a business imperative. But unconscious bias holds us back and de-biasing minds has proven to be difficult and expensive. Behavioral design offers a new solution. Iris Bohnet shows that by de-biasing organizations instead of individuals, we can make smart changes that have big impacts--often at low cost and high speed."--Provided by publisher
The promise of behavioral design -- Part 1. The problem. Unconscious bias is everywhere ; De-biasing minds is hard ; Doing it yourself is risky ; Getting help only takes you so far -- Part 2. How to design talent management. Applying data to people decisions ; Orchestrating smarter evaluation procedures ; Attracting the right people -- Part 3. How to design school and work. Adjusting risk ; Leveling the playing field -- Part 4. How to design diversity. Creating role models ; Crafting groups ; Shaping norms ; Increasing transparency ; Designing change.
Includes bibliographical references (pages 293-364) and index.
Keywords: Sex discrimination in employment; Gender mainstreaming; Organizational behavior